Buying Interest in TikTok Shop: The Role of Live Streaming, Reviews, and Influencers - Nasikhin, Muh. Nur Ali Khoirun; Sundari, Ariefah; Syaikhuddin, Ahmad Yani; Tyas, Sekar Nining (Klabat Journal of Management, 2025)
This study aims to analyze the influence of live streaming, online customer reviews, and influencer marketing on consumer buying interest in the TikTok Shop application. The research was conducted at Darul Ulum Lamongan Islamic University using a quantitative approach, with a sample of 98 students selected through purposive sampling. Data were analyzed using partial and simultaneous tests with SPSS 26. The coefficient of determination test, based on the R Square value, revealed that live streaming, online customer reviews, and influencer marketing collectively influence consumer buying interest by 42.6%. The statistical analysis yielded the following findings: (1) live streaming, online customer reviews, and influencer marketing collectively impact consumer buying interest; (2) online customer reviews do not have a significant effect on consumer buying interest; (3) influencer marketing has a positive and significant influence on consumer buying interest; and (4) live streaming, online customer reviews, and influencer marketing, when considered together, significantly affect consumer buying interest. These findings highlight the critical role of influencer marketing and live streaming in shaping consumer behavior on the TikTok Shop platform, while online customer reviews appear to have a less significant impact.